Uma estratégia de marketing para o artesanato do Rio Grande do Norte: o programa integrado de desenvolvimento do artesanato sob forma cooperativista - Souza, Tereza de (1991)
The study of artisan activities in this thesis cIearIy showed the necessity of starting from an historical context of policies directed toword this activity as much at the national leveI as at the regional, for it is beIieved that only by this route will it be possible to bring forward and understand its diverse pubIics and markets. Thus, this study focusses on the integrated program of artisan development in Rio Grande do Norte in a cooperativist form, identifying the externaI and internaI interferences in the process of deveIoping the artisan product. It points outo problems and characteristics of the Rio Grande do Norte artisan sector and of the cooperativist system. It sp approaches the concepts of marketing for not for profit organizations and proposes a marketing strategy for the arts and crafts.